Flights of steps heading towards the Mandakini Kund - Temples of India Project Team (Jio Institute, 2024)
The Mandakini Kund is a square-shaped reservoir of sacred water with entrances on three sides. Flights of steps are provided on each side, facilitating access for people to descend into the holy water. On the fourth side of the reservoir, there is a visible flat-roofed structure supported by pillars. Moreover, there are two petite pavilions located at the corners of the reservoir.